Health and Nutritional Status Among Internally Displaced Children under Five Years, during the Civil War: Sri Lankan Experience - Thushara Madhuka Ambagahahage (Indonesian Journal of Public Health Nutrition, 2023)
AbstractAround the globe, 1 in 6 children become vulnerable to grave physical and mental violence, hunger, sexual assaults, and exploitation of human rights due to war. These adversities are multi-dimensional, synergistic, and often subtle. This study attempted to evaluate the health and nutritional status of children aged under five years and living in the war zone of Sri Lanka, in view of improving the health services delivered to them. The study used a descriptive cross-sectional design. The study sample, 400, was based on probability proportionate and then systematic sampling drawn from IDP camps located in the Vavuniya district. Validated instruments along with hemoglobin and anthropometry measurements were administered. Among children, more than half were malnourished based on weight for height z-score (WHZ) anthropometry index (<-2 SD) One-fourth had not received age-appropriate vaccinations. More than 50% had psychological symptoms. Maternal and Child Health service gaps were observed along with deficits in the curative service. Identifying and addressing these complex health and nutritional problems in a multi-sector collaborative manner is a priority; the main focuses are nutrition, vaccination, mental healthcare, and essential maternal care. Keywords: child health, malnutrition, mental health, war, displacement AbstrakDi seluruh dunia, 1 dari 6 anak rentan terhadap kekerasan fisik dan mental yang berat, kelaparan, kekerasan seksual, dan eksploitasi hak asasi manusia akibat perang. Masalah ini bersifat multi-dimensi, sinergis, dan seringkali tidak terlihat. Studi ini mencoba mengevaluasi status kesehatan dan gizi anak berusia di bawah lima tahun dan tinggal di zona perang Sri Lanka untuk meningkatkan layanan kesehatan yang diberikan kepada mereka. Penelitian ini menggunakan desain deskriptif cross-sectional. Sampel penelitian sebanyak 400 anak didasarkan pada probabilitas proporsional dan kemudian penarikan sampel sistematis dari kamp-kamp pengungsi yang terletak di Distrik Vavuniya. Instrumen yang divalidasi bersama dengan pengukuran hemoglobin dan antropometri juga dilakukan. Diketahui lebih dari setengah anak-anak mengalami malnutrisi berdasarkan indeks antropometri Berat Badan menurut Tinggi Badan (BB/TB)(<-2 SD). Seperempatnya belum menerima vaksinasi sesuai usia. Lebih dari 50% memiliki gejala psikologis. Kesenjangan layanan Kesehatan Ibu dan Anak terobservasi bersama dengan kurangnya layanan kuratif. Mengidentifikasi dan mengatasi masalah kesehatan dan gizi yang kompleks ini dengan cara kolaborasi multisektor merupakan prioritas; fokus utamanya adalah gizi, vaksinasi, perawatan kesehatan mental, dan perawatan ibu yang esensial. Kata Kunci: kesehatan anak, malnutrisi, kesehatan mental, perang, pengungsian